A study on the impact of ESG performance, corporate resilience on total factor productivity - S. Lan; O.Zh. Zhadigerova; A.B. Assanova; N.Sh. Syrlybayeva (Хабаршысы. Экономика сериясы)
The aim of this study is to examine the impact of total factor productivity (TFP) on corporate performance, considering the sustainability of the company, including its ESG (Environmental, Social, and Governance) indicators, which have a significant influence on TFP. In a global environment marked by uncertainty, companies with high ESG scores demonstrate greater adaptability and resource allocation efficiency, contributing to the growth of TFP.